Pedagogi Ilahi: Pandangan Origen tentang Pengaruh Pembacaan Kitab Suci sebagai Pembentuk Nilai Kehidupan - Casthelia Kartika (Indonesian Journal of Theology, 2019)
Discussion concerning how the Scriptures form the basis for growth in the spiritual life of believers figures quite centrally in the thought and theology of Origen of Alexandria (185-250 CE). Origen encourages every Christian to read the Scriptures for the purpose of fostering a refinement of the soul and for the shaping of a spiritual life within the believer’s own self, in order for them to continue in growth toward attaining perfect maturity of life that is to be found in their communion with Christ. To achieve that goal, Origen asserts, the reading of Scripture must be carried out within a framework of divine pedagogy.